Social Interaction and Purchasing Decisions: a Sociological Approach to Environmental Influence - Welly Surjono (Program Studi Pendidikan IPS, 2025)
Social interactions play an important role in influencing individuals' purchasing decisions in the context of modern society. This study examines how the social environment, consisting of family, friends and reference groups, significantly shapes consumer preferences and behaviour. Through a sociological approach, this study explores theories of social interaction and its influence on purchasing decisions, including mechanisms of conformity, social group influence and normative pressure. By analysing consumer behaviour within their social networks, this research highlights how social norms, group status, and cultural and environmental expectations can influence product and brand choices. The results show that the social environment not only influences purchasing decisions directly through daily interactions, but also through the construction of individual social identities. Consumers often seek social validation through the products they buy, hoping to gain recognition or status within their social group. In addition, phenomena such as shifts in consumption behaviour due to the influence of social media and opinion leaders also strengthen the impact of the social environment on purchasing decisions. This research confirms the importance of considering aspects of social interaction in marketing strategies, especially in understanding consumer motivation from a sociological perspective. The findings provide practical implications for marketers in designing campaigns that can leverage social dynamics to influence consumer preferences and drive more effective purchase behaviour.